Phospholipase A2 enhances the endothelial cell detachment effect of a snake venom metalloproteinase in the absence of catalysis - Bustillo, Soledad (2015)
Fil: Bustillo, Soledad. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.